KETENTUAN FORCE MAJEURE DALAM KONTRAK BISNIS PADA MASA PANDEMI COVID-19 - Liza Nofianti (Justici, 2023)
ABSTRACT During the Covid-19 Pandemic, the aim is to find out whether theThe Covid-19 pandemic which the government has designated as a national disaster can be classified as a force majeure in the implementation of business contracts during the covid-19 pandemic as a national disaster. Library Research is research conducted in libraries, where data is obtained from available data by reading, studying books, laws and regulations, magazines, scientific works, legal dictionaries, and so on. The corona pandemic is used as the argument for force majeure in a business contract based on Presidential Decree Number 12 of 2020 concerning Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (Covid-19). This reason is used as the debtor's defense for the non-performance of a contract due to something that cannot be predicted.